Polyvinyl Alcohol Films Reinforced with Nanocellulose from Rice Husk - Gabriel Monteiro Cholant; Mariane Weirich Bosenbecker; Alexandra Augusta Reichert; Cesar Augusto Gonçalves Beatrice; Thales Castilhos Freitas; Naurienni Dutra Freitas; Nathalia Vieira Villar de Nunes; Alexandre Ferreira Galio; André Luiz Missio; Amanda Dantas de Oliveira (Macromol)
Progress in the field of biodegradable materials has been significantly accelerated in recent years, driven by the search for sustainable substitutes for fossil-derived resources. This study investigates the formulation of biodegradable films composed of polyvinyl alcohol (PVA) and nanocellulose extracted from rice husk. The rice husk underwent alkaline treatment and bleaching for cellulose extraction, followed by sulfuric acid hydrolysis to obtain nanocellulose. The cellulose and nanocellulose were characterized through Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Thermogravimetric Analysis (TGA). Films of pure PVA and those reinforced with 1 wt. % of nanocellulose were prepared using the solvent casting method. The evaluations showed that the modulus of elasticity and tensile strength of the PVA/nanocellulose films were increased by 295.45% and 29.6%, respectively, compared to the pure PVA film. The PVA/nanocellulose film exhibited the lowest solubility and water vapor permeability. Optical Microscopy confirmed a flawless surface for the nanocellulose-reinforced film, while the cellulose- and rice husk-reinforced films displayed irregularities. In the biodegradability assessment, the nanocellulose-reinforced film was the only one that withstood the experimental conditions. The results highlight the effectiveness of nanocellulose in enhancing PVA properties, making these films promising for sustainable packaging applications.